Dual role of microorganisms in metal corrosion: a review of mechanisms of corrosion promotion and inhibition - Li, Qianwei; Gong, Lingli; Chen, Xiaoji; Gadd, Geoffrey Michael; Liu, Daoqing (Frontiers in Microbiology, 2025)
The dual role of microorganisms in metal corrosion and corrosion inhibition reflects their complex biochemical interactions. In terms of corrosion, certain microorganisms accelerate metal oxidation by producing acidic metabolites or facilitating electrochemical processes, thereby causing damage to the material. Conversely, under specific conditions, they can form biofilms and/or biominerals that create protective layers, reducing the oxidation rate and delaying corrosion. This paper provides a comprehensive illustration of microbial corrosion promotion and inhibition, emphasizing the importance of key microorganisms involved in these corrosive processes. Microorganisms, including sulfate-reducing bacteria, nitrate-reducing bacteria, iron-oxidizing and iron-reducing bacteria and certain fungi, contribute to corrosion through their metabolic activities. Microbial corrosion mechanisms can be classified into extracellular electron transfer, microbial metabolism corrosion and the oxygen concentration cell theory. In contrast, microorganisms can effectively mitigate metal corrosion through a range of mechanisms including reduction of dissolved oxygen levels, secretion of antimicrobial substances, biological competition and biomineralization. Microbial corrosion and inhibition generally arise from multiple mechanisms working together, rather than a single cause. A deeper understanding of these mechanisms can provide a theoretical basis and practical guidance for the development of new anti-corrosion strategies.